BEVACIZUMAB VS RANIBIZUMAB IN MACULAR EDEMA DUE TO RETINAL VEIN OCCLUSION: SHORT-TERM OUTCOMES - Kurniawan, Chalid (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2024)
Introduction and Objective: Bevacizumab or Ranibizumab was widely used as therapy for macular edema (ME) in retinal vein occlusion (RVO) and diabetic retinopathy. The purpose of this study was to comparing short-term outcomes for patients who received intravitreal Bevacizumab (IVB) injection or Ranibizumab (IVR) for ME due to RVO Methods: This was observational, cross sectional study comparing patients received IVB or IVR. Primary outcomes data (visual acuity and central macular thickness/CMT) and secondary outcomes data (number injection and intra ocular pressure/IOP) were collected at baseline and 3 months after injection Results: There were 4 eyes in each group. There were no significant difference in mean change of visual acuity (-0.2750.25 vs -0.150.5 logMAR; p=0.676) and CMT (-171.50 129.08 vs -98.2537.67 m; p=0.345) in IVB vs IVR groups. There were also no significant difference in mean change of IOP (22.16 vs 24.69 mmHg; p=1) and number of injection (2.250.50 vs 1.750.9; p=0.401 ) in both groups. Conclusion: In short-term both IVB and IVB have relative similar outcomes on increasing visual acuity and decreasing CMT in ME due to RVO